2022
DOI: 10.1128/spectrum.02402-22
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Dictyostelid Cellular Slime Molds, Including Two Species New to Science, in Forest Soils of Changbai Mountain, China

Abstract: Dictyostelium robusticaule and Heterostelium recretum are two new species of dictyostelids reported in this study. The potential use of atp1 sequences is a complement of SSU rDNA sequences for the identifying dictyostelids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…The Jaccard similarity coefficient (S J %) of the family, genus, and species was calculated using data obtained from Changbai Mountain (CB) [ 23 ] in Jilin Province, Gushan Mountain (GS) [ 42 ] in Fujian Province, Baiyun Mountain (BY) [ 43 ] in Henan Province, Qinghai–Tibet Plateau in Tibet (QT) [ 22 ], and the Fanjing Mountain Nature Reserve (FJ) in Guizhou in the present study ( Figure 13 A). At the family level, the majority for each other (S J %) was higher than 50%, reaching moderate similarity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Jaccard similarity coefficient (S J %) of the family, genus, and species was calculated using data obtained from Changbai Mountain (CB) [ 23 ] in Jilin Province, Gushan Mountain (GS) [ 42 ] in Fujian Province, Baiyun Mountain (BY) [ 43 ] in Henan Province, Qinghai–Tibet Plateau in Tibet (QT) [ 22 ], and the Fanjing Mountain Nature Reserve (FJ) in Guizhou in the present study ( Figure 13 A). At the family level, the majority for each other (S J %) was higher than 50%, reaching moderate similarity.…”
Section: Resultsmentioning
confidence: 99%
“…Dictyostelium purpureum ( Figure 7 ), with large, robust sorocarps and deep purplish sori, is a cosmopolitan species reported from Africa, across North America, and in many localities in Asia [ 45 ]. Dictyostelium robusticaule , with the species name referring to its robust sorophores, was first reported by Zou et al [ 23 ] from a mixed forest on Changbai Mountain, China. In this study, the species was isolated from a broadleaf forest, and SSU rRNA phylogeny places it in a highly supported clade together with D. robusticaule (GenBank accession no.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientific studies have found that mixed forests are particularly interesting for resistance against the uncertainties of extreme climate development, as higher structural complexity and species interactions can be expected to be less affected in these forests compared to monospecific ones ( 59 , 60 ). In a recent study, Zou et al ( 41 ) studied the diversity of dictyostelids in Changbai Mountain of China and found that mixed broadleaf–conifer forests produced more isolates and species than broadleaf forests at the same elevation and also had the highest species richness. It is remarkable that D. giganteum and D. sphaerocephalum were reported again from farmland, consistent with previously reported species by Stephenson and Rajguru in agricultural soils in the United States ( 5 ).…”
Section: Discussionmentioning
confidence: 99%